Election Night: Karen Humphrey Elected Mayor of Fresno - Watkins, Howard::::::::: (1989)
L to r: Les Kimber, ? Pauline Kimber, Karen Humphrey, Craig Scharton, Anne Kinzel, Chris Petersen and Chris Petersen